2013
DOI: 10.3389/fnbeh.2013.00119
|View full text |Cite
|
Sign up to set email alerts
|

Neudesin is involved in anxiety behavior: structural and neurochemical correlates

Abstract: Neudesin (also known as neuron derived neurotrophic factor, Nenf) is a scarcely studied putative non-canonical neurotrophic factor. In order to understand its function in the brain, we performed an extensive behavioral characterization (motor, emotional, and cognitive dimensions) of neudesin-null mice. The absence of neudesin leads to an anxious-like behavior as assessed in the elevated plus maze (EPM), light/dark box (LDB) and novelty suppressed feeding (NSF) tests, but not in the acoustic startle (AS) test. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
2
20
0
1
Order By: Relevance
“…Turnover rates of 5-HT and DA (5-HIAA/5-HT as well as HVA/DA and DOPAC/DA, respectively) were calculated as indices of serotonergic and dopaminergic activity, respectively. Monoamine turnover rates are more reliable indices of neurotransmission activity than absolute levels of monoamine, as they integrate synthesis, release, reuptake, and metabolism of neurotransmitters in the synapse (56 (95% O 2 , 5% CO 2 )]. Both extracellular recordings [Multiclamp 700B amplifier (Axon Instruments) and borosilicate glass pipettes with saline (3-5 MΩ)] and stimulation (bipolar tungsten electrode) were performed in the middle of the stratum radiatum of CA1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Turnover rates of 5-HT and DA (5-HIAA/5-HT as well as HVA/DA and DOPAC/DA, respectively) were calculated as indices of serotonergic and dopaminergic activity, respectively. Monoamine turnover rates are more reliable indices of neurotransmission activity than absolute levels of monoamine, as they integrate synthesis, release, reuptake, and metabolism of neurotransmitters in the synapse (56 (95% O 2 , 5% CO 2 )]. Both extracellular recordings [Multiclamp 700B amplifier (Axon Instruments) and borosilicate glass pipettes with saline (3-5 MΩ)] and stimulation (bipolar tungsten electrode) were performed in the middle of the stratum radiatum of CA1.…”
Section: Methodsmentioning
confidence: 99%
“…Reverse-phase ion pairing chromatography was used to assay monoamines and their metabolites using an Aquasil C18HPLC column (250 × 4.6 mm, 5 μm; ThermoElectron). Samples were quantified by comparison of the area under the curve against known external reference standards using a PC-compatible HPLC software package (Chromatography Station) as previously described (56). The limit of detection was 1 pg/20 μL (injection volume).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Byerly et al reported that the administration of recombinant neudesin to the hypothalamus repressed appetite. Novais et al generated neudesin knockout (KO) mice and reported that deletion of the neudesin gene resulted in increased anxious-like behavior caused by insufficient development of hippocampal neurons 21) . These results showed that neudesin is crucial for neuronal development and function.…”
Section: Introductionmentioning
confidence: 99%